Study of 11 BMI-associated loci identified in GWAS for associations with central obesity in the Chinese children. - Bo Xi; Hong Cheng; Yue Shen; Giriraj R Chandak; Xiaoyuan Zhao; Dongqing Hou; Lijun Wu; Xingyu Wang; Jie Mi (PLoS ONE, 2013)
OBJECTIVE: Recent genome-wide association studies have identified many single nucleotide polymorphisms (SNPs) associated with body mass index (BMI)/generalized obesity. In this study, we aimed to examine the associations of identified SNPs with risk of central obesity in a child population from China. METHODS: We genotyped 11 SNPs (FTO rs9939609, MC4R rs17782313, GNPDA2 rs10938397, BDNF rs6265, FAIM2 rs7138803, NPC1 rs1805081, SEC16B rs10913469, SH2B1 rs4788102, PCSK1rs6235, KCTD15 rs29941, BAT2 rs2844479) in the Chinese children (N = 3502, age range 6-18 years) from the Beijing Child and Adolescent Metabolic Syndrome (BCAMS). Based on the age- and sex- specific waist circumference (WC) standards generated in the BCAMS study, 1196 central obese cases and 2306 controls were identified. RESULTS: Of 11 studied SNPs, four SNPs and genetic risk score (GRS) based on them were statistically significantly associated with central obesity by WC criteria (FTO rs9939609: OR = 1.29, 95%CI = 1.10-1.50, p = 0.001; MC4R rs17782313: OR = 1.27, 95%CI = 1.12-1.44, p = 1.32×10⁻⁴; GNPDA2 rs10938397: OR = 1.22, 95%CI = 1.09-1.37, p = 4.09×10⁻⁴; BDNF rs6265: OR = 1.20, 95%CI = 1.08-1.34, p = 8.86×10⁻⁴; GRS: OR = 1.25, 95%CI 1.16-1.34, p = 2.58×10⁻⁹) after adjustment for sex, age, pubertal stage, physical activity and family history of obesity. Similar observations were made using weight-to-height ratio (WHtR) criterion. However, other SNPs were not associated with central obesity by WC as well as WHtR criterion. CONCLUSIONS: Our study replicates the statistically significant association of four SNPs (FTO rs9939609, MC4R rs17782313, GNPDA2 rs10938397, BDNF rs6265) with risk of central obesity in the Chinese children.